Dancing eye syndrome as first symptom of neuroblastoma - Venturelli, Cristina; Guerra, Azzurra; Paolucci, Paolo; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2013)
Background: “Dancing eye syndrome”, also called Kinsbourne syndrome or Opsoclonus-Myoclonus-Ataxia Syndrome (OMS) is a rare neurological disorder that in children is frequently associated to occult, low-grade neuroblastoma (NB) (>50% of the cases). OMS may also be triggered by infections and it is often associated to developmental impairment and disability.Case presentation: We discuss the case of a 16 months old female with acutely onset of OMS associated to occult stage III NB.Conclusions: OMS represents a diagnostic challenge for pediatric clinicians. The suspect of OMS imposes the search for an occult NB in order to promptly treat a life-threatening event like tumor and to prevent the neurological sequels linked to OMS.